The Influence of Pasture and Non-pasture-Based Feeding Systems on the Aroma of Raw Bovine Milk - Clarke, Holly J.; Fitzpatrick, Ellen; Hennessy, Deirdre; O'Sullivan, Maurice G.; Kerry, Joseph P.; Kilcawley, Kieran N. (Frontiers in Nutrition, 2022)
Aroma-active compounds in raw bovine milk produced from cows fed perennial ryegrass (GRS) or cows fed total mixed ration (TMR) consisting of grass silage, maize silage and concentrates were identified by direct immersion sorptive extraction (DI Hi-Sorb) coupled with gas-chromatography-mass spectrometry and olfactometry using odour intensity and aroma extraction dilution analysis. Ninety nine volatile organic compounds (VOC) were identified in these raw GRS and TMR milk samples, 33 of which were also present in the feed and rumen samples from these diets. Only the abundance of 13 VOC varied significantly with diet. However, the odours of both raw milks were quite distinct as aroma perception is not only influenced by abundance alone, but also by the odour activity of each VOC. Approximately thirty percent of the VOC influenced the aroma perception of these raw milks. This study clearly highlighted the significant impact of VOC transferring from the diet that influenced the aroma perception of both GRS and TMR raw milk. The aroma of the raw TMR milk was more complex than that of the raw GRS milk, and many of the key dietary derived odour active VOC influencing the aroma of raw TMR milk, likely arose during the production of the TMR feed as most were either derived from Maillard reactions or impacted by heat. Seventeen of the forty four odour activities detected differed between both sample types. This study has clearly demonstrated the impact of diet on the aroma perception of raw bovine milk.